2014
DOI: 10.1007/s10620-014-3282-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of PRKCDBP, A Novel Transcriptional Target of TNF-α, and Its Downregulation by Infliximab in Patients with Ulcerative Colitis

Abstract: These results demonstrate that mucosal expression of PRKCDBP correlated strongly with TNF-α expression in UC patients and that IFX therapy resulted in profound reductions in both PRKCDBP and TNF-α. Thus, these findings support that PRKCDBP expression is tightly controlled by TNF-α, and the anti-inflammatory effect of IFX may in part stem from blockade of the TNF-α-PRKCDBP signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“… 17 In this previous study, we demonstrated that, PRKCDBP expression is tightly controlled by TNF-α in patients with moderate to severe UC. 17 Along with our previous result, considering that PRKCDBP is a proapoptotic tumor suppressor and a transcriptional target of TNF-α, it seems probable that these missense SNPs could generate variant protein products, with varying levels of biological activity. Nevertheless, the association between the SNPs of PRKCDBP and susceptibility to IBD has not yet been determined.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“… 17 In this previous study, we demonstrated that, PRKCDBP expression is tightly controlled by TNF-α in patients with moderate to severe UC. 17 Along with our previous result, considering that PRKCDBP is a proapoptotic tumor suppressor and a transcriptional target of TNF-α, it seems probable that these missense SNPs could generate variant protein products, with varying levels of biological activity. Nevertheless, the association between the SNPs of PRKCDBP and susceptibility to IBD has not yet been determined.…”
Section: Discussionmentioning
confidence: 81%
“…The possible mechanism of the association between PRKCDBP and susceptibility to IBD has not been established. Based on our previous study, 17 we speculated that PRKCDBP may play a role in the inflammatory processes controlled by TNF-α in IBD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In view of the loss of cavin3 in numerous cancers (Caren et al, 2011;Kim et al, 2014;Lee et al, 2008;Lee et al, 2011;Martinez et al, 2009;Tong et al, 2010;Xu et al, 2001;Zochbauer-Muller et al, 2005) and the crucial role of BRCA1 as a tumor suppressor (King et al, 2003;Miki et al, 1994;Venkitaraman et al, 2002), these studies describing a new functional partner for BRCA1 suggest that cavin3 should be considered in future diagnostic and therapeutic strategies. (Z-Leu-Leu-Leu-al, Cat no.…”
Section: /07/20mentioning
confidence: 99%
“…Cavin3 belongs to a family of proteins that includes caveolaeassociated protein 1 (cavin1), caveolae-associated protein 2 (cavin2), and the muscle-specific member caveolae-associated protein 4 (cavin4) (Ariotti and Parton, 2013;Bastiani et al, 2009;Hansen et al, 2009Lo et al, 2015;McMahon et al, 2009). Cavin3 is a putative tumor suppressor gene that is epigenetically silenced in a range of human malignancies (Xu et al, 2001), principally due to hypermethylation of its promoter region (Caren et al, 2011;Kim et al, 2014;Lee et al, 2008;Lee et al, 2011;Martinez et al, 2009;Tong et al, 2010;Zochbauer-Muller et al, 2005). Furthermore, cavin3 has previously suggested to interact with BRCA1, although no data has been formally published to support this interaction (Xu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%